Slovenske grajske stavbe in leto 1945 - Lazarini, Franci (Studia Historica Slovenica, 2016)
The article discusses destiny of Slovenian castles and mansions after 1945, when due to the change of the political system the attitude of politics and public towards the castles and mansions changed radically. The result was a systematic detriment and neglecting of the castles and mansions, an important factor for their bad condition was also the new, unsuitable use of the buildings. In addition to the attempts of some art historians (especially France Stele) to protect at least some of the castles and mansions, the article also presents the destiny of the furnishings of the castes and mansions (artworks, furniture, books), especially the work of Federal Collecting Centre, which was established with the purpose of collecting and transfer of cultural goods from the confiscated buildings.
Keywords: 1945; gradovi; knjige; nacionalizacija; razlastitev; revolucija; Slovenija; socializem; stanovanjska oprema; umetnine; zaplemba premoženja